Comparative Evaluation of Therapeutic Efficacy of Oral Tranexamic Acid versus its Intradermal Administration in Melasma – A Quasi-Experimental Study - Malik, Asma; Shahid, Muhammad Farhan; Ahmad, Muhammad Khurram; Khadam, Noman; Manzoor, Tayyaba (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the therapeutic efficacy of oral tranexamic acid versus transdermal tranexamic acid administration in patients with melasma.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Dermatology, Pak Emirates Military Hospital (PEMH), Rawalpindi Pakistan, May to Oct 2024.Methodology: The study enrolled 104 patients with diagnosed melasma, who were divided in a 1:1 ratio into two groups, Group A and Group B. Informed consent was taken from all patients. Group A received intralesional tranexamic acid while Group B took oral tranexamic acid 250mg twice a day. Modified Melasma Area and Severity Index (mMASI) was calculated for each patient at baseline and monitoring of both groups was done on a monthly basis with mMASI for 3 months.Results: The median age of this sample was 35.22±9.83 years, comprising 95(91.30%) females and 9(8.70%) males. Median baseline mMASI for Group A was 18.6(5.85) and for Group B, it was also 18.6(5.85). Comparison from baseline mMASI score showed a consistent reduction in mMASI scores at each follow-up (p=0.00). In our study population, 49(94.23%) patients in the intralesional group responded to treatment, whereas 47(90.38%) patients responded to treatment in the oral tranexamic acid group (p=0.72).Conclusion: Both routes of tranexamic acid administration demonstrated high response rates with np statistically significant differences.